Frequency of Rotavirus and Adenovirus in Turkish and Immigrant Patients with Acute Gastroenteritis - Altay-Koçak, Aylin; Dinç, Bedia; Özkan, Merve; Gülbahçe-Orhan, Sultan; Çolak, Meryem; Bozdayı, Gülendam; Ahmed, Kamruddin (Cerrahpaşa Medical Journal, 2024)
Objective: The objective of this study was to investigate the prevalence and seasonal distribution of rotavirus and enteric adenovirus in patients with acute gastroenteritis. Methods: The results of 2960 patients admitted to Ankara Training and Research Hospital with gastroenteritis between March 2018 and August 2019 were investigated retrospectively. A chromatographic immunoassay (Rotavirus and Adenovirus Combo Rapid Test, General Diagnostica Inc., Rancho Cucamonga, CA, USA), detecting both viruses simultaneously, was used according to the manufacturer’s instructions. Results: Of the 2960 patients, 1286 (43.4%) were female, 1674 (56.6%) were male, and 2873 (97.7%) and 87 (2.3%) were under 18 years old and 18 years and older, respectively. The number of Turkish and refugee patients was 2590 (87.5%) and 370 (12.5%), respectively. Viral antigens of 281/2960 (9.5%) were positive for rotavirus, and 54/2960 (1.8%) were positive for adenovirus. Of the Turkish patients, 243/2590 (9.4%) were rotavirus positive, and 51/2590 (1.9%) were adenovirus positive. Among the refugee patients, 38/370 (10.3%) were rotavirus positive, and 3/370 (0.8%) were adenovirus positive. The highest prevalence of rotavirus and adenovirus, according to age groups, was determined at 12-36 months of age (25.3%) and 49-59 months of age (3.2%), respectively. The highest prevalence of rotavirus and adenovirus positivity was in spring (17.8%) and in autumn (2.9%), respectively. Conclusion: Rotavirus is the most common cause of gastroenteritis during infancy and childhood. Additionally, enteric adenovirus is an important cause of gastroenteritis during this period. Since these viral infections may have serious complications, rapid diagnosis is important, and detection of both viruses among various populations may be useful for epidemiological purposes. Cite this article as: Altay-Koçak A, Dinç B, Özkan M, et al. Frequency of rotavirus and adenovirus in Turkish and immigrant patients with acute gastroenteritis. Cerrahpaşa Med J. 2024;48(1):30-33.